Penerapan Athiti Krama Dalam Peningkatan Mutu Pendidikan Agama Hindu Pada Pasraman Dharma Bhakti Gianyar - Oka Silantari, I Gusti Ayu; Mardika, I Ketut (Jurnal Penjaminan Mutu, 2018)
In human nature, apart from being individual beings as well as social beings who have their own culture. Culture arises in humans due to reason and thought in the human being itself. Humans will be able to live perfectly when they live together with other humans, in relation to other humans, certain norms or rules are needed. In the regulation, one of them was written about the procedure for honoring guests called Athiti Krama. Athiti Krama gives motivation in human life because through this human being can foster good relations between humans one with other human beings in harmony. The implementation of Athiti Krama can be found in societies everywhere in the world, both in the advanced society and the people who are still modest in their civilization. In social life, everyone should behave well so as to create happiness for themselves and the community, because in the teachings of Hinduism, Athiti Krama teachings are basically contained which can bring people to achieve harmony in social order in society. The basis of Athiti Kramas teachings is the ethics or morality that many of the Vedic scriptures have mentioned, one of which is Tri Kaya Parisudha. Considering the importance of Athiti Krama as a social guide in peoples lives. So it should be known to be applied in the learning process in Pasraman Dharma Bhakti.